Micro turbo expander design for small scale ORC Tesla turbine - Talluri, Lorenzo (Premio Tesi di Dottorato, 2020)
The Tesla expander was first developed by N. Tesla at the beginning of the 20th century. In recent years, due to the increasing appeal towards micro power generation and energy recovery from wasted flows, this cost effective expander technology rose a renovated interest. In the present study, a 2D numerical model is realized and a design procedure of a Tesla turbine for ORC applications is proposed. A throughout optimization method is developed by evaluating the losses of each component. The 2D model results are further exploited through the development of 3D computational investigation, which allows an accurate comprehension of the flow characteristics. Finally, two prototypes are designed, realized and tested. The former one is designed to work with air as working fluid. The second prototype is designed to work with organic fluids. The achieved experimental results confirmed the validity and the large potential applicative chances of this emerging technology in the field of micro sizes, low inlet temperature and low expansion ratios.